Experiments in general chemistry - Murov, Steven L. (Brooks/Cole-Thomson Learning, 2004)
This workbook lab manual focuses not only on what happens during chemical reactions, but also helps students understand why chemical reactions occur. The sequence of 35 experiments follows topics covered in most general chemistry texts as outlined in a correlation chart to several of the publisher's general chemistry titles. The fifth edition adds the synthesis and empirical formula determination of zinc iodide, and deletes the use of iron.